2011
DOI: 10.1097/bot.0b013e318206fa99
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Popliteal Artery Injury Risk With Locked Lateral Plating of the Tibial Plateau

Abstract: The Synthes 4.5-mm plate can put the popliteal artery at risk with as little as 3-mm posterior liftoff in the intended straight lateral position or with 5-mm anterior plate translation with no posterior liftoff. Therefore, placement of the 4.5-mm plate in the proper position and confirmation of its position with a true lateral radiograph is paramount to avoid injury to the popliteal artery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 13 publications
0
14
0
Order By: Relevance
“…In their experimental study, Dee M et al . raised a particular concern about popliteal artery injury in LCP. We encountered no cases of popliteal artery injury.…”
Section: Discussionmentioning
confidence: 89%
“…In their experimental study, Dee M et al . raised a particular concern about popliteal artery injury in LCP. We encountered no cases of popliteal artery injury.…”
Section: Discussionmentioning
confidence: 89%
“…In addition, if precise attention is not paid, neurovascular structures posterior to the tibia may be jeopardized during surgical procedures [2][3][4]. During surgical procedures, possible major complications that could jeopardize final clinical outcomes include tibial plateau fractures [5], dislocation of the osteotomy hinge [3,6], and under-or overcorrection of the tibial slope [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Fracture maps and heat maps demonstrated that the uncaptured areas tended to locate around the rim of the posterolateral wall of the tibial plateau and distributed in the posterior 1/2 to 3/4 of the fibula head’s parallel position ( Figures 4,5 ). Without a suitable or well-designed internal fixation ( 16 , 17 , 21 ) and with the block of the special anatomical structures ( 3 , 4 ), the exposure of posterolateral tibial plateau is difficult in the surgery, and the reduction and fixation of posterolateral fragments are challenging for orthopedists. Therefore, it is noteworthy that a combination of plates or a design-improved plate should be used to increase the possibility of capturing posterolateral fragments if the fragment locates in the high-frequency uncaptured region mentioned above.…”
Section: Discussionmentioning
confidence: 99%
“…The surgical treatment of posterolateral tibial plateau fractures is fraught with challenges, one of which is the lack of consensus on internal fixations for the posterolateral plateau. Since the periphery of the posterolateral column is blocked by the fibular head, large muscles and ligaments, and the important neurovascular bundles in the popliteal fossa ( 3 , 4 ), accordingly, it is relatedly challenging for surgeons to expose the posterolateral column through posterolateral surgical approaches and place a small posterolateral buttress plate ( 5 - 7 ), and no unanimous and definitive conclusion on treatment strategy can be drawn ( 8 , 9 ). Nevertheless, the extended anterolateral approach with an anterolateral plate remains the most common and least risky method of fixing posterolateral fractures currently ( 7 , 10 ).…”
Section: Introductionmentioning
confidence: 99%